Prévalence de la surcharge pondérale (surpoids et obésité) en milieu scolaire urbain à Kamsar République de Guinée. [Prevalence of overweight and obesity in urban schools in Kamsar Republic of Guinea] - Ibrahima K. BARRY; Ibrahima CONDE; Emmanuel CAMARA; Marie E. HYJAZI; Moustapha KOUYATE (Nutrition & Santé, 2020)
Introduction. Overweight is a consequence of nutritional transitions, seden-tarity lifestyle, and poverty. Objective. To determine the prevalence of overweight in schools. Population and methods. This was a descriptive cross-sectional study, uni and bi varied analytics, and logistic regression. The CHI2 of Pearson, and Wald have been ap-plied. Odds ratio (OR), and risk factors were estimated. Results. Data concerned 300 children (49% of boys), with a sex ratio of 1.02, an average age of 14 (±2 years), and an overweight of 25%. Factors associated with overweight were ethnicity type [P - 0.000 (OR to 95%) 1.00 (0.000 – 2.000)], gender [P - 0.006 (OR to 95% CI) 2.00 (1.000 – 3.000)], family history: obesity [P - 0.000 (OR to 95% CI) 3.00 (1.000 – 6.000)], high blood pressure (HBP) [P - 0.015 (OR to 95% CI) 1.00 (1.000 – 3.000)],type 2 diabetes (T2D) [P - 0.002 (OR to 95% CI) 2.00 (1.000 – 4.000)], meals number [P - 0.000 (OR to 95% CI) 3.00 (2.000 – 6.000)], activities by week [P - 0.000 (OR to 95% CI) 4.00 (2.000 – 7.000)], and age [P - 0.000 (OR to 95% CI) 7.00 (4.068 –12.000)]. Conclusion. Overweight is high in boys. Family history, as obesity, T2D, HBP, meals number, lacks of activities increase this risk. [Introduction. La surcharge pondérale est une conséquence des transitions nutritionnelles, de la sédentarité et de la pauvreté. Objectif. Déterminer la prévalence de la surcharge pondérale en milieu scolaire. Population et méthodes. C’est une étude transversale descriptive, analytique en uni,bi variés et régression logistique. Les CHI2 de Pearson, de Wald ont été appliqués. Des odds ratio (OR) et les coefficients de risque ont été estimés. Résultats. Les données concernaient 300 enfants (49% de garçons), avec un sex ratio de 1,02, d’âge moyen de 14 (±2ans), avec une surcharge pondérale de 25%. Les facteurs associés étaient le type d’ethnie [P=0,000 (OR à IC à 95%) 1,00 (0,000 – 2,000) ], le genre [P=0,006 (OR à IC à 95%) 2,00 (1,000 – 3,000)], les antécédents familiaux : l’obésité [P=0,000 (OR à IC à 95%) 3,00 (1,000 – 6,000)], l’hypertension artérielle (HTA) [P=0,015 (OR à IC à 95%) 1,00 (1,000 – 3,000)], le diabète de type 2 (DT2) [P=0,002 (OR à IC à 95%) 2,00 (1,000 – 4,000)], le nombre de repas [P=0,000 (OR à IC à 95%) 3,00 (2,000 – 6,000)], les activités par semaine [P= 0,000 (OR à IC à 95%) 4,00 (2,000 – 7,000)] et l’âge [P=0,000 (OR à IC à 95%) 7,00 (4,068 –12,000)]. Conclusion. La surcharge pondérale est plus élevée chez les garçons. Les antécédents familiaux, tels que l’obésité, le DT2, l’HTA, le nombre de repas et l’absence d’activités augmentent ce risque.]